PERAN BIMBINGAN BELAJAR ORANG TUA TERHADAP DISIPLIN BELAJAR SISWA - Bella Elvira; Elly Sukmanasa; Tatang Muhajang (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2019)
THE EFFECT OF PARENTAL TUTORING ON STUDENT DISCIPLINE The purpose of this study was to determine the effect of parental tutoring on student learning discipline. The data of this study were obtained using a questionnaire instrument for both variables. The validity test of the instrument of social interaction and discipline is calculated using the Pearson Product Moment Correlation Coefficient formula and the reliability coefficient is calculated using the Cronbach Alpha formula. The population in this study were the fifth grade students of Cibeureum 4 Public Elementary School in Bogor City, amounting to 89 students. The samples taken by 47 students were obtained using the Taro Yamane formula. Tests for analysis prerequisites in the form of a normality test (Liliefors). After the normality test, homogeneity (Fisher) was tested. Data that has been declared normal and homogeneous is used to test the hypothesis, the results of which show that there is an influence of parents' tutoring on student learning discipline. Simple correlation regression analysis technique produces a relationship model which is expressed in the form of a regression equation that is Ŷ = 9.99 + 0.86X, with a tcount of 17 greater than t table with a real level of 0.05 of 2.021 and a contribution based on research results of 86 %. Based on the results of the above research, it can be concluded that there is an influence of parents' tutoring on the discipline of learning in grade IV students at Cibeureum 4 Elementary School in Bogor City 2018/2019.